The Relationship Between Work Posture and The Incidence of Myalgia Among Farmers - Yunita R.M.B Sitompul; Wendy Hendrika (International Journal of Health Engineering and Technology, 2025)
Myalgia or muscle pain is a common symptom experienced by individuals who perform work with improper body posture for prolonged periods, particularly in the agricultural sector. This study aims to determine the relationship between work posture and the incidence of myalgia among the community in Cisampih Village, Sumedang Regency, in 2023. The research employed an analytic descriptive design with a cross-sectional approach. The sample was selected using total sampling, consisting of 51 farmer respondents. Data were analyzed using the chi-square test with a significance level of α = 0.05. The results showed a significant relationship between work posture (p-value = 0.018), length of service (p-value = 0.018), and duration of work (p-value = 0.003) with the incidence of myalgia among farmers. The conclusion of this study is that work posture, length of service, and duration of work have a significant effect on the occurrence of myalgia. These findings highlight the importance of preventive efforts through the application of ergonomic work postures and balanced work schedules to reduce the risk of myalgia among farmers. Keywords: Myalgia, Work Posture, Length of Service, Working Hours